Media management and digital transformation - Bygdås, Arne L. 1971-; Clegg, Stewart; Hagen, Aina Landsverk (Routledge, 2019)
Media Management and Digital Transformation provides novel and empirically rich insights into the tensions, struggles and innovations of news making and managing in media organizations. From an empirically grounded perspective this book investigates how the 'buzz' of new technology tends to prevent management from seeing which changes are needed and indeed possible to make in the newsroom. It presents ground-breaking research showing that fostering ingenious, innovative solutions can be created from within organizations by engaging and allowing employees to recognize problems, reflect and experiment with new ways of working, using technology as support for change. The research presented arises from a four-year action research project in collaboration with three small and medium-sized Norwegian newspapers, in addition to ethnographic research in newsrooms and on media organizations and phenomena in the USA and Europe